Nurses' Perspectives on Delivering Compassionate Care - Oluyomi, Zoe (2014)
Abstract Current literature and policy documents emphasise compassion as an essential professional value within nursing. However, there have been growing concerns about a perceived lack of compassion in nursing care leading to detrimental effects on patients’ hospital experience. Therefore, there is a need to gain insight into why some nurses are perceived as uncompassionate, why this kind of behaviour might occur and how it can be overcome. Several factors can arise within the hospital setting which can impede compassionate care. In order to investigate this further, this study explored nurses’ perceptions of compassionate care and the factors that prevent its delivery in the acute hospital setting. A qualitative approach was undertaken, using in-depth semi-structured interviews with fifteen nurses in one acute hospital. All interviews were audio-recorded and transcribed verbatim. The data was then analysed manually using thematic content analysis. Four main themes were identified in the data; understanding the nature of compassion, personal characteristics, achieving an emotional balance, and training and education. The nurses recognised compassion as integral to patient care. The interpersonal interactive aspects of care between the nurse and patients impacted on the delivery of compassionate care, as well as the demands of the emotional investment required in maintaining these very short-term relationships with patients. This study thus highlights the importance of nurses having the emotional resources to provide compassionate care. In addition, factors relating to the organisational culture of the environment significantly contributed to the nurses’ emotional imbalances and feelings of exhaustion, which consequently hindered compassionate care giving. Although limitations to this study have been acknowledged, the study highlighted the need to address the extent to which the current NHS culture supports nurses to deliver compassionate care. More emphasis vi should also be placed on compassion within nurse education and training in order to facilitate compassionate practice.